2018
DOI: 10.1044/2018_lshss-stlt1-17-0138
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Statistical Learning in Understanding and Treating Spoken Language Outcomes in Deaf Children With Cochlear Implants

Abstract: We suggest that understanding how statistical learning contributes to spoken language development is important for understanding some of the difficulties that children who are deaf and use cochlear implants might face and argue that it may be beneficial to develop novel language interventions that focus specifically on improving core foundational statistical learning skills.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 115 publications
0
15
0
Order By: Relevance
“…Moreover, the shorter the interval between the two implantations, the better the children’s language performance. Similarly, Guo et al (2015) found that at 1 year after implantation, children with bilateral CIs, but not children with unilateral CIs, demonstrate sensitivity to statistical characteristics of words comparable to that of children with NH during the early stages of lexical development (for a review on statistical learning abilities of CI users, see Deocampo et al 2018 ). There is also evidence suggesting that children who receive simultaneous bilateral implantation perform better than their unilaterally implanted peers do on measures of verbal reasoning ( Jacobs et al 2016 ).…”
Section: Benefits Of Bilateral Cochlear Implantationmentioning
confidence: 98%
“…Moreover, the shorter the interval between the two implantations, the better the children’s language performance. Similarly, Guo et al (2015) found that at 1 year after implantation, children with bilateral CIs, but not children with unilateral CIs, demonstrate sensitivity to statistical characteristics of words comparable to that of children with NH during the early stages of lexical development (for a review on statistical learning abilities of CI users, see Deocampo et al 2018 ). There is also evidence suggesting that children who receive simultaneous bilateral implantation perform better than their unilaterally implanted peers do on measures of verbal reasoning ( Jacobs et al 2016 ).…”
Section: Benefits Of Bilateral Cochlear Implantationmentioning
confidence: 98%
“…SL is defined as the ability to process or learn patterns of environmental stimuli such as spoken language, music, or one’s motor action, which unfolds in time and usually occur unconsciously. [ 12 13 14 ] It is assumed that early performance on SL tasks could be used for predicting language outcomes from a very young age. [ 15 ] SL is considered an important mechanism for the acquisition of spoken language in recent studies.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] SL is considered an important mechanism for the acquisition of spoken language in recent studies. [ 14 ] Moreover, studies on normal children (NC) have indicated that there is direct correlation between SL and language acquisition. [ 16 ] Visual sequence learning (VSL) (VSL is one of SL tasks, it is explained in detail in method section) in 6 months old as well as 8½ months old infants showed a relation between SL and vocabulary acquisition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research suggests that some of the language delays and variability in outcomes observed in DHH children could be due to individual differences in sequential processing (Anderson, 2014; Deocampo, Smith, Kronenberger, Pisoni, & Conway, 2018; Pisoni, Kronenberger, Chandramouli, & Conway, 2016; Uddén & Bahlmann, 2012). Sequential processing itself can refer to two types of skills.…”
mentioning
confidence: 99%